Coverage of Famine and Starving Children In the Press (1917-1924) - Shohrukhbek Mamadaliev (International Journal on Integrated Education, 2023)
In this article, the details of the famine that occurred in Turkestan in 1917, the fate of starving people and starving children who were deported from Russia in 1921 due to the famine were tried to be covered based on press materials. Particularly, daily news and articles about the issue of famine were objectively analyzed on the pages of the newspapers as "Ulug Turkistan", "Bashkiristan News", "El Bayrogi", "Ishtrokiyun", " Ozod Sibir", "Fergana ".